The Protruding Ear: Cosmetic and Reconstruction - Ali, Kausar; Meaike, Jesse D.; Maricevich, Renata S.; Olshinka, Asaf (Seminars in Plastic Surgery, 2017)
Ear prominence is a relatively common cosmetic deformity with no associated functional deficits, but with profound psychosocial impact, especially in young patients. Protruding ears in children have propagated surgical advances that incorporate reconstructive techniques. Here we outline a systematic framework to evaluate the protruding ear and present various reconstructive surgical options for correction. Both cosmetic and reconstructive perspectives should be entertained when addressing this anatomical deformity.
Keywords: protruding ear; prominent ear correction; otoplasty; cosmetic; reconstruction